Autonomic dysfunction and primary antiphospholipid syndrome: a frequent and frightening correlation? - Bilora, Franca (Dove Medical Press, 2012)
INTRODUCTION: the correlation between primary antiphospholipid syndrome (APS) and cardiovascular events is well known, but the correlation between APS and sudden death is not clear; it probably correlates with sympathetic alterations of the autonomic system. AIM: To compare the autonomic nervous system (ANS) in a group of subjects suffering from APS against that of a control group with no cardiovascular risk factors, matched for age, sex, and body mass index. SUBJECTS AND METHODS: An equal number (n = 31) of subjects with APS, and healthy controls, underwent autonomic evaluation: tilt test, deep breath, Valsalva maneuver, hand grip, lying-to-standing, Stroop, and sweat tests. RESULTS: Cases in the APS group were positive for the tilt test, relating to changes in respiratory rate intervals, by comparison with controls. Results of other tests were also altered significantly in APS cases, by comparison with controls. (The sweat and Stroop tests were only performed in 14 cases). Autonomic disease did not correlate with age, sex, history of disease, arterial or venous thrombosis, or antibody positivity; only their coagulation parameters correlated with autonomic dysfunction. CONCLUSION: Autonomic dysfunction in APS seems to correlate with coagulation parameters. APS patients should receive autonomic evaluation, to minimize the risks of fatal arrhythmias and sudden death.